1990
DOI: 10.1901/jeab.1990.54-23
|View full text |Cite
|
Sign up to set email alerts
|

Tacting and Manding in Correspondence Training: Effects of Child Selection of Verbalization

Abstract: We investigated correspondence between verbal and nonverbal behavior in preschool children in a play setting. Four children (4 years old) participated in a multiple baseline across subjects design. Children were asked what toy(s) they were going to play with during an immediately upcoming play period. When no contingencies were placed on either verbal or nonverbal behavior, children showed high rates of correspondence. When children were required to verbalize about a toy from a restricted range of infrequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
28
0
7

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 13 publications
0
28
0
7
Order By: Relevance
“…Correspondence was, however, reinstated when reinforcement was made contingent on corresponding reports. Baer and Detrich (1990) found similar results when children were asked to report on future rather than previous behavior (say-do correspondence). Ribeiro (1989) concluded that during the baseline condition, reports functioned as tacts, verbal operants under discriminative control of the speaker's previous playing behavior, and established through generalized reinforcement (cf.…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…Correspondence was, however, reinstated when reinforcement was made contingent on corresponding reports. Baer and Detrich (1990) found similar results when children were asked to report on future rather than previous behavior (say-do correspondence). Ribeiro (1989) concluded that during the baseline condition, reports functioned as tacts, verbal operants under discriminative control of the speaker's previous playing behavior, and established through generalized reinforcement (cf.…”
mentioning
confidence: 63%
“…These studies measured both the reports and the behaviors reported (usually nonverbal behaviors), so that the correspondence between them could be assessed and the effect of controlling variables investigated (e.g., Baer and Detrich 1990;Lima and AbreuRodrigues 2010;Luciano et al 2001;Ribeiro 1989;St. Peter et al 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Entretanto, a publicação de Verbal Behavior (Skinner, 1957) demorou a gerar testes experimentais, sendo precedidos nos anos 1970 por estudos focalizando a emergência de classes de estímulos equivalentes (Sidman, 1971;Sidman & Cresson, 1973;Sidman, Cresson & Wilson-Morris, 1974), muito importantes por demonstrarem o controle de estímulos envolvido nos processos considerados simbólicos. Nas décadas seguintes surgiram estudos sobre a correspondência entre dizer e fazer visando, entre outros objetivos teóricos, investigar a dependência ou independência funcional entre mandos e tactos (e.g., Baer & Detrich, 1990;Freitas-Ribeiro, 1989) e sobre processos adicionais envolvendo controle verbal (e.g., Baer, Detrich & Weninger, 1988;Deacon & Konarski, 1987;Guevremont, Osnes & Stokes, 1986;Ward & Stare, 1990). Tendo em vista que essas áreas de pesquisa promovem a compreensão dos processos considerados simbólicos como efeitos do controle de estímulos e, deste modo, demonstram empiricamente sua natureza operante, alguns serão brevemente sumariados para, na discussão geral, explorar suas relações com o presente estudo.…”
unclassified
“…A maioria dos primeiros estudos utilizou seqüências fazer-dizer (e.g., Israel & O'Leary, 1973;Karoly & Dirks, 1977;Paniagua & Baer, 1982;Roger-Warren & Baer, 1976). Os estudos mais recentes utilizam seqüências promessa-fazer (e.g., Baer, 1990;Baer & Detrich, 1990) e, além de questionarem os primeiros procedimentos, introduziram novas questões tais como: critério funcional para demonstrar correspondência e generalização, medidas de linha de base, respostas verbais funcionais e encadeamento de respostas no treino de correspondência (Lloyd, 2002). Talvez os primeiros estudos sobre comportamento verbal tenham sido nesta agora consagrada área de correspondência entre fazer-dizer, iniciados no final da década de 1960 (Risley e Hart, 1968 (Baum, 1994;Simonassi & Cameschi, 2003;Skinner, 1969).…”
unclassified